On a local solvability and stability of the inverse transmission eigenvalue problem. (23rd October 2017) - Bondarenko, Natalia; Buterin, Sergey
Abstract: We prove a local solvability and stability of the inverse transmission eigenvalue problem posed by McLaughlin and Polyakov (1994 J. Diff. Equ .107 351–82). In particular, this result establishes the minimality of the data used therein. The proof is constructive.